Pisara - Centeno, Fatima Marie Monteagudo 1993- (2018)
"Lisa, a young passionate teacher, prepares her requirements for her job interview in Manila when Nika, a quiet but curious transfer student from Surigao, shakes her focus. With language and culture as barriers between confusion and enlightenment, Pisara will test Lisa's perspective, ideals, and dreams as an educator and as a citizen of her nation as she learns more and more about Nika. This film, through the lens of multicultural education theory, aims to shed light on the lack of inclusivity surrounding the education system of our postcolonial multicultural country. It also tries to address the collective ignorance educational institutions impose on students and tries to present a discussion on how we as a society could replace this ignorance with open arms and unhindered understanding of our rich and evolving culture."